UJI STANDAR KINERJA PENGELOLAAN TAMAN NASIONAL GUNUNG HALIMUN SALAK PADA PRINSIP KELESTARIAN FUNGSI SOSIAL BUDAYA - Allan Rosehan; Arzyana Sunkar; Sambas Basuni (Department of Forest Resources Conservation and Ecotourism - IPB University, 2010)
The current national park management did not fully take into account the sustainability of socio cultural benefits, particularly for indigenous communities. Therefore the park’s performance achievement on the aspect of socio cultural required to be assessed by using tested management standards. The research objectives were: (1) to measure the actual verifier and assess the indicators formulated by the Directorate General of Forest Protection and Nature Conservation and Bogor Agricultural University in Gunung Halimun Salak National Park (GHSNP), (2) to analyze the validity of management performance indicators of GHSNP (3) to measure the achievement of each indicator based on a minimum standard of performance, and (4) to formulate recommendations for improving management standards. The results showed that: (1) the actual value of management performance indicators for GHSNP was good for one indicator and fair for four indicators. There were four indicators that could not be measured and assessed; (2) eight of the nine indicators which have been tested in the field were valid; (3) the achievement of performance indicators for GHSNP management on the principle of socio-cultural sustainability has achieved its minimum values; and (4) the standard management of national park should be completed because field results showed that, there were difficulties measuring the verifiers and assessing the indicators. This research found that there were inconsistency on the terminology used in the standards, lack of operational definition, difficulty in using the norm, and verifier inappropriate with actual condition. Keywords : criteria, indicators, performance management standards, national parks, socio cultural